Microencapsulation of bioactive volatile compounds from MD2 pineapple peel Extract using spray-drying and foam-mat drying - Nur Liyana Nordin; Jamilah Bakar; Noranizan Mohd Adzahan; Ahmad Faizal Abdull Razis; Norsharina Ismail; Rabiha Sulaiman (Journal of Agriculture and Food Research)
Pineapple peel extracts constitute bioactive compounds that degrade due to light, oxidation, and moisture. This study aimed to encapsulate cellulase-treated MD2 pineapple peel extracts ensuring stability of bioactive compounds-rich extracts in the form of powders. Two drying methods were employed including spray-drying (150 °C) and foam-mat drying (60 °C) using maltodextrin (5 % v/v and 10 % v/v) and gum Arabic (GA) (5 % v/v and 10 % v/v) as carrier agents. Spray-drying for all microencapsulated powders exhibited high-quality powder with lower water activity (0.35–0.44), particle size diameters (D50) ranging from 19.7 to 53.71 μm and higher solubility index (75.42–98.53 %) in comparison to foam-mat drying. Spray-drying using 10 % GA exhibited the highest encapsulation efficiency (EE%) of above 99 % and further extraction of different phenolic fractions is shown to be the most efficient encapsulation of insoluble-bound phenolic (IBP). Bioactive volatile compounds comprised of 2-Methoxy-4-vinylphenol and Phenol, 2,4-bis(1,1-dimethylethyl) in the microcapsules of 10 % GA. Cellulase-treated MD2 pineapple peel extract powder containing 10 % GA exhibited low in toxicity effect (IC50 > 1000 μg/mL) against NIH3T3 fibroblast cells. Microcapsule powder from bioactive-rich extracts of cellulase-treated MD2 pineapple peel has the potential to be used in functional foods, nutraceuticals, pharmaceuticals, and cosmetics ingredients.